2001
DOI: 10.1016/s1526-9523(00)00096-9
|View full text |Cite
|
Sign up to set email alerts
|

Hidden From View: Violent Deaths Among Pregnant Women in the District of Columbia, 1988–1996

Abstract: Medical examiner autopsy records identify violent pregnancy-associated deaths, many of which occur early in pregnancy and are missed by other enhanced case-finding techniques that require a record of a birth or fetal death. These deaths are usually excluded from reported maternal mortality ratios. Few studies have evaluated the prevalence of homicide in women of childbearing age, yet understanding the extent of less commonly associated causes of death during pregnancy such as homicide, may lead to improved ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
55
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 26 publications
5
55
0
1
Order By: Relevance
“…One study has suggested that the risk of homicide may be higher in early pregnancy 21 and, thus, the higher rate of hospital visits early in pregnancy could be a proxy for more severe nonfatal assaults during this early period. Regardless, the higher rates of assault visits early in pregnancy justify beginning prevention initiatives before pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…One study has suggested that the risk of homicide may be higher in early pregnancy 21 and, thus, the higher rate of hospital visits early in pregnancy could be a proxy for more severe nonfatal assaults during this early period. Regardless, the higher rates of assault visits early in pregnancy justify beginning prevention initiatives before pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Studies 5,9,14,23 show that the causal link between violent death and pregnancy/postpartum is not easily identifi ed in investigations. In this study, it was decided to classify them as related to pregnancy.…”
Section: Iml Householdmentioning
confidence: 99%
“…If domestic violence was behind the death of a pregnant woman or one who had recently given birth, such deaths should be investigated and classifi ed as maternal deaths from indirect obstetric causes. 5,9,14,23 Although the relationship between suicide and pregnancy is a controversial topic in the literature, some authors have shown the existence of an association at the same time as they question its exclusion from the construction of maternal death indicators. 20,23 In some suicide cases, the pregnancy does not appear; in others, they represent unsuccessful attempts to abort a pregnancy which could not be legally terminated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports of gunshot wounds to pregnant women, occasionally injuring the gravid uterus, are becoming more common (1)(2)(3). Gunshots during pregnancy clearly jeopardize both the fetus and the mother.…”
Section: Introductionmentioning
confidence: 99%